'Fight the reds, support the blue': Blue Lives Matter and the US counter-subversive tradition. (July 2021) - Shanahan, Jarrod; Wall, Tyler
In the wake of the rightwing siege of the US Capitol, which put 'Blue Lives Matter' supporters at odds with police protecting the Capitol, the authors look to the history and contours of the 'counter-subversive tradition' in the United States and its locus in local police departments. They examine a similar moment of social unrest – the mid-to-late 1960s – and the pro-police organising undertaken by Support Your Local Police (SYLP), a front group of the ultra-right John Birch Society, which blended anti-communism with opposition to the Black Freedom Movement, with particular anxiety about the spectre of united white and black revolt from below and the encroachment of the federal government on local power from above. The campaign also presented a kind of uniquely rightwing anti-statism, largely through the rejection of impediments to local powers and, specifically, the untrammelled power of the cops. In making sense of the Capitol siege, and the years of rightwing organising that preceded it, the article argues that this important precursor to 'Blue Lives Matter' presents a schema for understanding longstanding efforts in police organising in defence of what James Baldwin called 'arrogant autonomy' – freedom from civilian oversight or political challenges to cop power, and from all challenges to locally entrenched structures of white power.